Effect of Continuing Professional Development on Self-Efficacy for Nurses: A Cross-Sectional Study - Mukhlid Alshammari (The Journal of Continuing Education in Nursing, 2026)
Background: Self-efficacy is crucial for nursing performance and is influenced by factors such as education, experience, and continuing professional development (CPD). This study explored the impact of CPD on the self-efficacy of nurses in Saudi Arabia. Method: A cross-sectional study was conducted among 183 nurses across three health care facilities in Eastern Saudi Arabia. Self-efficacy was measured with the General Self-Efficacy Scale (GSE), and CPD was assessed with the Arabic adaptation of the Questionnaire for Professional Development of Nurses. Results: Mean GSE score was 30.11 ( SD = 4.54), indicating high self-efficacy. Significant positive correlations were found between GSE and age ( r = .181, p = .014), years of experience ( r = .201, p = .006), and motivation for professional development ( r = .398, p < .001). Regression analysis identified age, motivation for professional development, professional accountability and workplace engagement activities, and graduate nursing education as significant positive predictors of GSE. Conclusion: Domains of CPD, including motivation for professional development and engagement in professional accountability and workplace activities, were significant predictors of nurses' self-efficacy in Saudi Arabia. These findings support structured CPD initiatives that foster motivation and engagement to strengthen nursing practice and patient care outcomes.